Village Elite Role on The Productive Migrant Village Program in Banyumas Indonesia - Muslihudin, Muslihudin; Wulan, Tyas Retno; Sugiarto, Tri; Wardhianna, Sotyania; Wijayanti, Sri (Universitas Negeri Semarang, 2021)
Within social structure inside society, there is a group called the elite group consists of small number of people who are at the top of the stratum of the community. The group has a big role in various activities in the community. Banyumas is one of the regencies that receive a Productive Migrant Village Program (PMVP) whose implementation is related to the group of village elite. The purpose of this paper is to show how the role of the village elite in the village community empowerment, especially in the implementation of the programs. The method of the research is a critical qualitative research method. The data are obtained by interview, observation, and documentation. An analysis of the study was conducted interactively. The results of the study are; 1) The implementation of the programs are driven by village elites, 2) village political elites are responsible for the success since the beginning of the program, 3) political elites and economic elites ally in the implementation of the productive migrant village program. Such pattern of village elite alliances can be used as a useful model for the success of development programs or the empowerment of rural communities, not only in the programs, but also in other community empowerment programs.